Analisis Pemilihan Supplier Kemasan Karton Pada Produk Multivitamin Dengan Menggunakan Metode Analytical Hierarchy Process (AHP) dan Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) - Manulang, Dea Amelia; Yuliarty, Popy (Universitas Mercu Buana, 2021)
In this research, analyzing the supplier selection of carton is by using the Analytical Hierarchy Process (AHP) and Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) methods. The AHP method is used in making an assessment through pairwise comparisons between elements accurately to determine the weight of each alternative and to test the consistency of each respondent against each criterion and alternative. The results obtained from the AHP method are InterCriteria 0.01, Quality 0.03, Cost 0.04, Delivery 0.01, Flexibility 0.003, and Responsiveness 0.09. This proves that the value of the Consistency ratio (CR) ≤ 0.1% means that the data is correct and is considered consistent. Meanwhile, the Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) method is used to rank each alternative. The results obtained from the TOPSIS method are based on ranking sequentially, namely PT PBA 0.77, PT ARP 0.50, and PT DAI 0.47.